Relation between the barrier effect and partial discharge activity in the three-layer dielectrics; Proceedings of the 13th International Symposium on High Voltage Ingineering (Delft, Netherlands, August 25-29, 2003) - Gefle O. S.; Lebedev S. M.; Pokholkov Y. P. Yuri Petrovich; Agoris D. P.; Vitellas I. (2003, 2003)
В фонде НТБ ТПУ отсутствует